Asymmetry of the Oil Price Pass –Through to Inflation in Iran - Nazariyan, Rafik; Amiri, Ashkan (International Journal of Energy Economics and Policy, 2014)
Due to the structure of Iran’s economy, oil revenues do not have a multi-dimensional role rather than a one-dimensional role in inflation. To put it differently, oil revenues impact inflation through exchange rate, government budget, importation, and imported inflation, monetary base, GDP growth, and government investment. These factors sometimes have contradictory effects on inflation. Therefore, investigating and analyzing the pass-through of oil shocks into inflation and providing appropriate policies is quite essential. Hence, the present research is primarily aimed at modeling the pass-through of oil price and investigating its effect on inflation by means of hidden co-integration approach, analysis, and presenting political implications to control the effect of oil shocks on inflation. In order to do so, monthly data of crude oil and consumer price index from March 2003 to March 2013 have been utilized. The findings demonstrated the pass-through of oil price to the CPI in Iran. Moreover, the coefficient calculated in this study revealed that the magnitude of this pass-through is quite large in the long run in Iran’s economy. In addition, based on the CECM model which is a type of non-linear, asymmetric, and hidden co-integration method this research showed that the pass-through of oil price to inflation is asymmetrical. On the other hand, the dynamic short-term relationship, in the framework of CECM model, also confirmed the asymmetrical pass-through of positive and negative oil shocks into inflation. Keywords: oil price; inflation; Asymmetric Pass-Through; CECM model. JEL Classifications: C13; C22; E31; Q43